Potensi Pengembangan Pariwisata di Kabupaten Padang Lawas - Holijah, Siti; Sugianto; Aisyah, Siti (Jurnal Informatika Ekonomi Bisnis, 2023)
The tourism potential of hot springs in Padang Lawas Regency acts as a driving force for the economy of communities with low to medium economic levels. The people of Paringgonan Village depend on agriculture, so if this tourism is managed well it will have the potential for tourism development. This research aims to determine the tourism potential to be developed by the Tourism Office in Paringgonan Village. In this research, qualitative research methods were used with a descriptive approach. The data analysis technique applied is the interactive model introduced by Miles and Huberman, which includes the stages of data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of this research indicate that the potential for developing Hot Springs tourism has several supporting factors. There are tourist attractions such as hot springs, the availability of accommodation facilities such as hotels or inns, and the presence of mosques as important facilities. However, there are shortcomings in terms of road infrastructure to the Hot Springs and additional services. Apart from that, the efforts made by the Tourism Department to date have not reached their maximum potential. Therefore, in developing various tourist attractions in Paringgonan Village, there needs to be closer collaboration between the community and the local government, as well as improving facilities that can meet the needs of tourists who come to visit.